2020
DOI: 10.3390/min10100903
|View full text |Cite
|
Sign up to set email alerts
|

A Defect Study and Classification of Brown Diamonds with Deformation-Related Color

Abstract: For this study, the properties of a large sample of various types of brown diamonds with a deformation-related (referred to as “DR” in this work) color were studied to properly characterize and classify such diamonds, and to compare them to pink to purple to red diamonds. The acquisition of low temperature NIR spectra for a large range of brown diamonds and photoexcitation studies combined with various treatment experiments have opened new windows into certain defect characteristics of brown diamonds, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 23 publications
(34 reference statements)
2
25
1
Order By: Relevance
“…At the same time, the H3 system decreased and the H4 system, along with the 613 nm system, disappeared. The annealing temperature of the 613 nm system accorded with the published works [41,45,46]. The 490.7 nm center fell drastically as a result of annealing at 1500 • C and annealed out completely as a result of annealing at 1700 • C; this reflects the thermally activated diffusion of dislocations (Figure 6).…”
Section: Annealing Experimentssupporting
confidence: 77%
“…At the same time, the H3 system decreased and the H4 system, along with the 613 nm system, disappeared. The annealing temperature of the 613 nm system accorded with the published works [41,45,46]. The 490.7 nm center fell drastically as a result of annealing at 1500 • C and annealed out completely as a result of annealing at 1700 • C; this reflects the thermally activated diffusion of dislocations (Figure 6).…”
Section: Annealing Experimentssupporting
confidence: 77%
“…Both natural diamonds and CVD synthetic diamonds have the same refractive index, density, and appearance, and they have no distinct difference under a microscope. Obvious internal defects and stress lines might appear during the growth of natural diamonds due to the changes in external conditions [ 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Initial assignment of this band to dislocationrelated defects (Plotnikova et al, 1980) found some support in Mora et al (2002Mora et al ( , 2003. In a recent detailed investigation of PL spectra of deformed N-containing terrestrial diamonds (Hainschwang et al, 2020) it was suggested that the "700" nm band is a vibronic mode of a ZPL located at 620 nm, which, in turn, is clearly pronounced only at low temperatures. Whether the "700 nm" band from the later paper corresponds to features observed in yakutite or not is yet unknown, but in any case, its dislocation-related origin seems to be plausible.…”
Section: Photoluminescence Spectroscopymentioning
confidence: 95%